ACTUALIZATION OF CHARACTER VALUES IN HISTORY LEARNING IN SENIOR HIGH SCHOOL OF YOGYAKARTA - Febta Pratama; Aman Aman (Universitas Negeri Yogyakarta, 2017)
Abstract This research is aimed to: (1) identify character values which are actualized in history learning, (2) analyse the form of character values actualization which are actualized in history learning. This research is descriptive qualitative research with case study approach. Research sample is conducted using Purposive. Data analysis technique uses interactive analysis technique from Miles and Huberman which consist of data collection, data presentation and conclusion. The research findings show: (1) the values actualized in history learning are honesty, responsibility, love homeland, religious, discipline, curiosity, mutual respect, politeness, (2) the form of characteristic values actualization are statement admitting mistakes, congregation Zuhur pray, reciting Al-Quran, singing national anthem and hero songs before starting the lesson, attempting to get knowledge by asking. Keyword: actualization, character values, history learning, senior high school